Cascade Oxidation, Radical Addition, and Annulation of o‐Alkynylarylaldimine with Indole/Imidazopyridine: Access to Aromatic Heterocycle‐substituted Isoquinolines. Issue 6 (14th May 2020) - Zhao, Yun‐Hui; Yu, Yajun; Hu, Dandan; Zhao, Lang; Xie, Wenlin; Zhou, Zhihua
Abstract: A peroxide‐mediated oxidation/radical addition/cyclization cascade reaction for the construction of isoquinoline skeleton is reported. The mild metal‐free promoted conditions of this reaction allowed us to synthesize a library of aromatic heterocycle‐substituted isoquinolines with a broad substrate scope, good functional group tolerance, and high atom economy in moderate to good yields. The radical intermediate in this reaction system was captured by TEMPO and confirmed by mass spectrometry (TOF‐MS). Further In vitro antiproliferative activities exhibited significant inhibition of the growth of HepG2, MCF‐7, MGC803 and EC‐9706 human cancer cell lines. Abstract : A peroxide‐mediated oxidation/radical addition/cyclization cascade reaction for the construction of isoquinoline skeleton is reported. The mild metal‐free‐promoted conditions of this reaction allowed us to synthesize a library of aromatic heterocycle‐substituted isoquinolines with excellent antiproliferative activities.